On the role of productive government spendings for convergence of a growing economy with heterogenous specialists - Susanne Soretz; Ingrid Ott (Verein für Socialpolitik, 2010)
This paper employs a dynamic framework to compare the effects of alternative governmental activities on the process of convergence. Policy instruments include facilitating private investment and public expenditure (amount and structure) that act as enhancing individual skills. Highly skilled specialists are endowed with both technological and systemic skills, though to different extents. We analyze how governmental activity speeds up convergence thereby considering productivity growth at the technology frontier either as exogenous or as endogenous parameter. Which policy maximizes the speed of convergence is crucially affected by a country's state of development. A policy switch while catching-up may be preferable.
Keywords: O31; O33; J24; 330; productive governmental activities; technology frontier; convergence policies; higly-skilled specialists; technological skills; systemic skills